(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Today, during the advanced era of the digital economy, many networks have switched to online and have been connected to the Internet. Social media marketing is also part of the digital economy, and the demand for research in this area is growing. This article analyzes the conditions for online study of social media marketing in Uzbekistan and the design method of teaching. The following questions will be discussed: What are the conditions for learning how to marketing online social media? Also: What is the SWOT analysis on teaching social media marketing in Uzbekistan? To answer this question, a two-step research methodology was performed. The SWOT analysis analyzed the strengths, weaknesses, capabilities and potential risks of online social media marketing courses in the country.